LENGTH-WEIGHT RELATIONSHIP OF INTERTIDAL MOLLUSCS FROM MUMBAI, INDIA - Kulkarni, B. G.; Jaiswar, A. K. (Journal of Indian Fisheries Association, 2015)
A study on the length-weight relationship of common intertidal molluscs from Mumbai showed a high degree of correlation between their length and weight. Most of the molluscs exhibited isometric growth pattern but in some species, allometric growth was found, which is attributed to maturity, nonlinear growth of shell and the ecological conditions. The variations in the growth rate of Gafrarium divaricatum sampled from two geographically separate sites, Bandstand and NCP A, is a result of variation in eco ogical conditions. Key words: Length-weight, intertidal 1nolluscs